Síntese de materiais à base de TiO2, ZnO e SiO2: tratamento de áreas degradadas e efluentes - Gonçalves, Patrícia (2017)
The activities of the industrial and mineral sector are essential for the development of society, but they cause several environmental impacts, such as contamination of effluents by dyes and toxic metals. In order to mitigate these types of impacts, this study aimed to synthesize the materials TiO2, ZnO and SiO2, and its feasibility study of the application on the degradation of dyes by photocatalysis and removal of metals by adsorption. The oxides were synthesized by two methods: polymer precursors (PP) and sol-gel (SG). The materials obtained as powder were characterized by X-ray diffraction (XRD), specific surface area analysis by N2 physisorption (BET), field emission scanning electron microscopy (FEG-SEM), Fourier transform infrared spectroscopy (FTIR) and zeta potential. The synthesis method did not influence the crystalline phases of the obtained materials since ZnO presented wurtzite phase, TiO2 anatase and SiO2 presented amorphous characteristic. The materials showed low specific surface area, between 4 and 11 m2/g, except for SiO2 PP, which stood out with a specific surface area of 226 m²/g. By MEV-FEG, it was verified that for TiO2 and SiO2 higher average particle sizes were shown by SG methodology, whereas for ZnO, higher average particle size was obtained by PP. By FTIR, it was found that all the oxides presented their respective chemical groups related to the M-O bonds, but also presented organic residues of synthesis. Specific surface area and particle size variations were not significant in the photocatalytic response of the materials. On the other hand, the residues of synthesis on the surface of the particles justify the results of photocatalysis. This is because the degradation of Rhodamine B dye was the same for ZnO SG and ZnO PP (88%), and higher for TiO2 SG (90%) than TiO2 PP (80%). Regarding the adsorptive characteristics of the materials, the specific surface area and zeta potential analyzes deserve to be highlighted. By zeta potential, ZnO SG showed stability at pH above 10, and ZnO PP above 9.5; TiO2 SG presented stability at pH above 6, and TiO2 PP above 3; and SiO2 SG presented stability above 3.5, and SiO2 PP above 6. Adsorption tests of Mn2+ metal ions indicated that ZnO, SiO2, and TiO2 presented adsorbent potential. The best adsorption results were for the oxides at pH 8 and 8.5. SiO2 PP stood out in the adsorption tests, which presented higher adsorption of Mn2+ (Qm equal 1,49 mg/g) in 90 minutes of contact, pH 8.5, and 5 mg/L of adsorbent. This material presented higher specific surface area and stability in suspension in the pH 8.5, which justifies the higher adsorption presented in relation to the other oxides evaluated in this study.